The virtuous life in greek ethics - Reis, Burkhard (Cambridge University Press, 2013)
On 5 July 2006 Professor Dr Dorothea Frede will celebrate her 65th birthday. Professor Frede, who has held a chair of Philosophy at the University of Hamburg since 1991, is one of the outstanding scholars in the field of Ancient Philosophy, with a high reputation in Germany and the international academic community. She has published widely on Plato, Aristotle and the Hellenistic philosophers. She has also conducted research on Heidegger and phenomenology, Rorty and Davidson. Currently she is president of the German Society for Ancient Philosophy (GANPH). Recently she has been appointedMills Visiting Professor at the University of Berkeley, a position she will take up in 2006. Professor Frede’s birthday will also mark the end of her official activities in Hamburg. Friends and colleagues in Germany, England, the United States and Canada would like to use this occasion to offer her this volume and thereby to express their gratitude for her academic contributions and her friendship over the years